2007
DOI: 10.1111/j.1399-0012.2006.00616.x
|View full text |Cite
|
Sign up to set email alerts
|

Significance of microvascular thrombosis in renal allografts: role of ex vivo thrombolytic therapy

Abstract: Back table flush with activase rapidly lyses severe intraglomerular microthrombi making them successfully transplantable. Pre-treatment with activase seems to be an effective therapeutic intervention for kidneys with massive intraglomerular thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In two retrospective studies, Nghiem et al report the use of tPA in HTK for DCD kidneys with significant glomerular microthrombi burden. In the first study, tPA was added to a second ex vivo flush prior to engraftment for 12 kidney transplants, resulting in one graft loss (8%) and three patients (25%) with DGF . In the second study, tPA in HTK was utilized during MPP for similar kidneys with significant thrombosed glomeruli, but otherwise favorable findings, on biopsy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In two retrospective studies, Nghiem et al report the use of tPA in HTK for DCD kidneys with significant glomerular microthrombi burden. In the first study, tPA was added to a second ex vivo flush prior to engraftment for 12 kidney transplants, resulting in one graft loss (8%) and three patients (25%) with DGF . In the second study, tPA in HTK was utilized during MPP for similar kidneys with significant thrombosed glomeruli, but otherwise favorable findings, on biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Despite acceptable long‐term outcome data, DCD kidneys are at increased risk for delayed graft function (DGF), probably due to microthrombi and additional warm ischemia related to the withdrawal process . Typically, heparin is given before or at withdrawal of support, with a wait period of two to five min following cardiac death before organ recovery commences .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A potential option to reduce biliary injury and ITBS incidence is administering tissue plasminogen activator (tPA) into the HA to lyse microthrombi. Several studies have demonstrated this effect clinically, showing that tPA administration prior to liver reperfusion mitigates the risk of developing ITBS in DCD LT (11,(13)(14)(15)(16) and reduces intraglomerular microthrombi in renal allografts (17). However, a major concern with this approach in LT is transferring tPA activity from the donor liver to recipients, who are often already experiencing coagulopathy, Abbreviations: BE, biliary epithelium; BDI, bile duct injury; CBD, common bile duct; CIT, cold ischemic time; dPBG, deep peribiliary glands; DCD, donation after circulatory death; EVLP, ex-vivo liver perfusion; HA, hepatic artery; H&E, hematoxylin and eosin; IMB, intramural bleeding; ITBS, ischemic-type biliary strictures; LT, liver transplant; MS, mural stroma; NEDS, New England Donor Services; NMP, normothermic machine perfusion; pPBG, periluminal peribiliary glands; PV, portal vein; PVP, peribiliary vascular plexus; tPA, tissue plasminogen activator; tWIT, total warm ischemic time; fWIT, functional warm ischemic time; UW, University of Wisconsin; WIT, warm ischemic time.…”
Section: Introductionmentioning
confidence: 97%